SFRP5 Enhances Wnt5a Induced-Inflammation in Rheumatoid Arthritis Fibroblast-Like Synoviocytes - Mahmoud, Dorra Elhaj; Kaabachi, Wajih; Sassi, Nadia; Mokhtar, Amel; Moalla, Myriam; Ammar, Lobna Ben; Jemmali, Samia; Rekik, Sonia; Tarhouni, Lamjed; Kallel-Sellami, Maryam; Cheour, Elhem; Laadhar, Lilia (Frontiers in Immunology, 2021)
Background: Tissue derived fibroblast-like synoviocytes (td-FLS) are key actors in pannus formation and contribute to joint destruction and inflammation during rheumatoid arthritis (RA). Several members of the Wnt family, including Wnt5a, may contribute to RA td-FLS activation and can potentially serve as therapeutic targets. Objective: The present work aimed to investigate the expression of Wnt5a signaling elements in RA td-FLS and their potential precursors (fluid derived (fd) FLS and fibrocytes). We also studied the role of Wnt5a in RA td-FLS pro-inflammatory activity and whether the inhibitor SFRP5 could restore Wnt5a-induced synovial dysfunction in vitro. Materials and Methods: The levels of Wnt5a, SFRP5, Wnt5a receptors/coreceptors and Wnt5a pro-inflammatory targets were determined in cultured RA td-FLS, fd-FLS and fibrocytes using qPCR under basal conditions. The expression of pro-inflammatory molecules was assessed after RA td-FLS stimulation with Wnt5a and SFRP5 at different time points. Results: Our data showed that td-FLS, fd-FLS and fibrocytes from patients with RA expressed similar levels of Wnt5a and a set of Wnt5a receptors/coreceptors. We also demonstrated that Wnt5a stimulated the expression of the pro-inflammatory targets, especially IL1β, IL8 and IL6 in RA td-FLS. Wnt5a-induced inflammation was enhanced in the presence of SFRP5. Furthermore, Wnt5a alone and in conjunction with SFRP5 inhibited the gene expression of TCF4 and the protein levels of the canonical coreceptor LRP5. Conclusion: Wnt5a pro-inflammatory effect is not inhibited but enhanced by SFRP5 in RA td-FLS. This research highlights the importance of carefully evaluating changes in Wnt5a response in the presence of SFRP5.